Penerapan Model Pembelajaran Aktif Tipe Learning Start With A Questions (LSQ) Terhadap Hasil Belajar Peserta Didik pada Materi Perubahan Lingkungan Kelas X di SMA Negeri 1 Indralaya Utara - Willa Agustina; Yenny Anwar; Djunaidah Zen (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
The aim of this research was know the implementation of Learning Active Model of Learning Start With a Question (LSQ) towards Student Learning Outcomes on the subject of environment changes in SMA Negeri 1  Indralaya Utara. The research method used was Pre-Experimental with One Group Pretest Postest design. The sampling technique was done by purposive sampling technique. Data collection of learning result test was done in class X MIPA 1 with total of 29 students. The instrument used in this study is a matter of multiple choice which amounted to 30 questions. The t-test indicates that there is a significant difference between the value of the initial test and the final test of the learner at a 95% confidence level. The data analysis using SPSS obtained application tcount of 17.18 while ttable at 5% significance level with df 28 is 2,05. The result shows that tcount> ttable is 17,18>2,05. Student learning outcomes increase from before. This is evidenced from the average score of learning outcomes obtained in the initial test 44.69 while in the final test of 79.17, so H0 rejected, which means that there is influence of the application of active learning model type learning start with a question (LSQ) against learning outcomes of learners on the material changes of class X environment in SMA Negeri 1 Indralaya Utara.Key words : Learning Outcomes, LSQ, environmental change